(3eNJUQ cJGH GdYjfs - (3CHh YHO Gddg eMeO Hf YHO Gddg GdNWjH GdEScGais; (3GdNdjd Hf CMeO Hf YeQh Hf Jeje GdaQGgjOj GdCROj GdjMeOj, CHh YHO GdQMef,J (B170 (3g` s
(3ChdgG (B:s
(3cdGe GdYQH eHfi Ydi CQHYI CfMGA (B: (3GdKfGFi hGdKdGKi hGdQHGYi EdG Cf JdMbgG GdRhGFO , abO JHdZ HgG SHYI fMh GdbQYHdGfg hgj OhjHI s
(3BNQgG (B:s
(3aai GdChdi CUdjI LGA Ydi HfGFgG cGdZGjg hGdOGjg Je cJGH GdCda hGdhGh hGdjGA hgh BNQ cdGe GdYQH Je cJGH eNJUQ (B( (3cJGH (B) (3GdYjf , HMeO Gddg s
(3HChdgG JedcGJ CbOegG ai HZOGO SfI (B649 (3g`s
(3HgG CKQ WeSs
(3cJHJ ai MjGI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B112s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B219 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1443s
Keywords: (3GddZIs